Metal contaminations impact archaeal community composition, abundance and function in remote alpine lakes - Sergi Compte‐Port; Carles M. Borrego; Hélène Moussard; Mathilde Jeanbille; Claudia Ximena Restrepo‐Ortiz; Alberto de Diego; Azibar Rodriguez‐Iruretagoiena; Ainara Gredilla; Silvia Fdez‐Ortiz de Vallejuelo; Pierre E. Galand; Dimitri Kalenitchenko; Jean‐Luc Rols; et al. (Environmental Microbiology, 2018)
Summary Using the 16S rRNA and mcrA genes, we investigated the composition, abundance and activity of sediment archaeal communities within 18 high‐mountain lakes under contrasted metal levels from different origins (bedrock erosion, past‐mining activities and atmospheric depositions). Bathyarchaeota, Euryarchaeota and Woesearchaeota were the major phyla found at the meta‐community scale, representing 48%, 18.3% and 15.2% of the archaeal community respectively. Metals were equally important as physicochemical variables in explaining the assemblage of archaeal communities and their abundance. Methanogenesis appeared as a process of central importance in the carbon cycle within sediments of alpine lakes as indicated by the absolute abundance of methanogen 16S rRNA and mcrA gene transcripts (10 5 to 10 9 copies g −1 ). We showed that methanogen abundance and activity were significantly reduced with increasing concentrations of Pb and Cd, two indicators of airborne metal contaminations. Considering the ecological importance of methanogenesis in sediment habitats, these metal contaminations may have system wide implications even in remote area such as alpine lakes. Overall, this work was pioneer in integrating the effect of long‐range atmospheric depositions on archaeal communities and indicated that metal contamination might significantly compromise the contribution of Archaea to the carbon cycling of the mountain lake sediments.